Polymicrobial interactions between selected microbes of oral biofilm and differential expression of ALS genes and their related proteins / Ayesha Fahim - Ayesha, Fahim (2020)
More than 700 different types of microorganisms dwell in human oral mucosal surfaces. The interactions between these microorganisms contribute to formation of polymicrobial communities on hard and soft tissues as well as on dentures and implants. Candida albicans, a pleomorphic fungus inhabiting oral and gastrointestinal (GIT) mucosa becomes pathogenic in favourable conditions causing local or systemic disease. Since streptococci are early colonisers, the ability of Candida albicans to adhere to streptococci paves the way for an additional surface for candidal colonization and propagation. This study was aimed to investigate polymicrobial interactions between C. albicans, S. sanguinis and S. mitis on in-vitro oral biofilms and to identify differential expression of agglutinin-like sequence ALS1, ALS2, ALS3 genes and associated proteins. Single, dual and mixed species oral biofilms were formed in-vitro in static and dynamic flow conditions for 24 h. Biomass of each biofilm was determined using crystal violet (CV) stain and the cellular metabolic activity within these biofilms was assessed using tetrazolium XTT assay. Microbial growth of biofilms was calculated by counting colony forming units (CFU) on continuous flow model. The morphology of organisms in these biofilms was viewed under scanning electron microscope (SEM) and analysed using morphology index (Mi). The antimicrobial effect of amphotericin B, nystatin and chlorhexidine on each biofilm was seen by determining minimum inhibitory concentration (MIC). The expression of target genes in C. albicans was analysed by quantitative real-time PCR (qPCR) while their respective proteins by Western blot technique. CV and XTT analysis of static biofilms showed a significant increase in biomass and cellular metabolic activity of two dual species and mixed species in comparison to single species biofilm. The results were validated by CFU count of microorganisms on biofilms formed under continuous nutrient flow. SEM analysis revealed candida hyphae formed under the influence of streptococci in dual and mixed iv species biofilm, whereas, only blastoconidia were visible in single species. The MIC values of amphotericin B (AmB), nystatin (Nt) and chlorhexidine (CHX) was 4µg/mL against single species whereas the values were higher against dual and mixed species (64 and 125µg/mL respectively for AmB) (32 and 125µg/mL for Nt) (4 and 32µg/mL for CHX). The genomic expression revealed that ALS1 and ALS3 were significantly over expressed in mixed species biofilm, in comparison to dual species and single species biofilm. However, ALS2 was not significantly expressed in dual or mixed species. Western blot of single species showed clear bands of als1, als2 and als3p whereas, in dual and mixed species clear bands of only als1 and als3p were visible. In conclusion, C. albicans demonstrated enhanced biofilm characteristics when grown with S. mitis and S. sanguinis in both static and dynamic flow conditions. The role of ALS1 and ALS3 genes is enhanced in dual and mixed species. This study proposes substantial contribution of bacteria in propagation of C. albicans biofilm. Hence, in oral fungal infestations, promotion of the infection may be contingent upon the bacterial constituent, a prospect which is frequently neglected and requires more research.